Biomass production and macronutrient leaf content in zucchini grounded with biofertilizers in different soils (Research, Society and Development, 2020)
The reuse of livestock by-products in agricultural management is becoming an increasingly common and necessary practice, both for enabling good plant nutrition and for reducing fertilizer costs. In this way, the objective was to evaluate the biomass production and leaf contents of macronutrients of the Italian zucchini, hybrid Corona, cultivated in two soil types and fertilized with different biofertilizers. The experiment was conducted in pots in Fortaleza, Ceará. The design used was was randomized blocks in subdivided plots. The plots consisted of two soil types (S1: Alfisol Paleudalf soil and S2: Entisol Fluvent) and the subdivided plots of five aerobic fermentation biofertilizers (F1 = quail, F2 = sheep, F3 = bovine + quail + sheep, F4 = bovine and F5 = enriched crab), with five replicates. The analyzed variables were: shoot, root and total dry mass, and macronutrient leaf contents (nitrogen, phosphorus, potassium, calcium and magnesium). The Entisol fertilized with the mixed biofertilizer allowed higher values of shoot and total dry mass of zucchini plants compared to Alfisol and the other biofertilizers, root dry mass was higher when fertilized with mixed biofertilizer in both soils. The Alfisol allowed a greater contribution of leaf macronutrients (N, P, K and Mg) in zucchini plants mainly when associated with mixed and bovine biofertilizers. Leaf contents of Ca were higher when the zucchini was cultivated in Entisol, except when fertilized with sheep biofertilizer.